(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The economic, social-political, spiritual-ideological relations of Uzbekistan with the countries of Central Asia are analyzed socio-philosophically in the article. The conditions and factors affecting the formation of security, stability and harmonious neighborhood environment in Central Asia are indicated. In the article, all the processes that take place in the socio-political system of the society work proportionately, the activities of people in the socio-political processes are effective, the factors affecting their activation have an effect, the importance of Central Asia’s rich natural resources, strategic location, economic transport, logistics issues, Uzbekistan’s open and it was analyzed that thanks to his pragmatic policy, regional relations were restored, borders were opened, air, bus, and railway routes were restored, enriched with new routes, and relations between citizens were established. Integrative processes in Central Asia are socio-philosophically analyzed as a holistic process consisting of interdependence, connection and development process.